Developmental Trajectory of Depressive Symptoms from Early Childhood through High School in Children and Adolescents with a High Intellectual Potential - Laurence Vaivre-Douret; Soukaina Hamdioui (MDPI AG, 2023)
We aimed to explore the developmental trajectory of depressive symptoms in a national sample of French children with a high intellectual potential (HIP) seeking help from gifted organizations. Participants were drawn from a national retrospective survey sent to 1200 families with HIP children (IQ ≥ 130) from primary to high school and they answered a self-report questionnaire of a depression scale (MDI-C). The children's parents completed a self-report questionnaire collected on different stages of the child's school level, perinatality, psychomotor development, health, family's history, behavior, interpersonal relationships and daily activities, school performance, presence of learning disorders and remediation. Four hundred and twenty HIP children were eligible with an IQ ≥ 130 aged from 8 to 17 years-old, 49% with depressive symptoms and 51% with no depressive symptoms. Analysis of 136 variables from anamnestic fields based on the use of Spearman's ρ test (ρ) with a non-parametric correlations showed that "learning disabilities" are significantly related to depressive symptoms in different groups (primary p = 0.001, middle p = 0.02, high school p = 0.001) as well as "difficulties in psychomotor skills" during primary (p = 0.003) and middle school (p = 0.02). Good relationships with family as well as with peers are significantly negatively correlated with depressive symptoms from childhood to primary (p = 0.003) and high school (p = 0.02). Certain details of correlations between the MDI-C scale's subfactors and anamnestic variables were analyzed. The ANOVA test about the MDI-C scale showed provocation as a significant marker at middle school (F (1, 418) = 3.487, p = 0.03) and low self-esteem at high school (F (1, 418) = 3.337, p = 0.03). A holistic developmental approach allowed us to highlight the risk factors of depression with a developmental trajectory origin linked to disorders of social adjustment and psychomotor skills and to the importance of misdiagnosed learning disabilities because of giftedness. Our findings support the interest in an early identification of and intervention in depression risk to improve clinical decision making on the effect of giftedness on mental health outcomes.